Resting energy expenditure, metabolic and sex hormones in two phases of the menstrual and hormonal contraceptive cycles - Löfberg, I. E.; Karppinen, J. E.; Laatikainen-Raussi, V.; Lehti, M.; Hackney, A. C.; Ihalainen, J. K.; Mikkonen, R. S. (Medicine & Science in Sports & Exercise, 2024)
Introduction Resting energy expenditure (REE) may fluctuate during the menstrual cycle (MC), due to the physiological effects of estradiol (E2) and progesterone. This study examined changes in REE and metabolic hormones (leptin, ghrelin, thyroid hormones), and dietary intake in two hormonally distinct groups, naturally menstruating women (NoOC) and women using monophasic combined oral contraceptives (COC).